Odpowiedź:
x = l-4 * [tex]\sqrt[3]{64}[/tex]l * (-0,25[tex])^{2}[/tex] + [tex]\frac{1}{3}[/tex] * [tex]\sqrt{9}[/tex] = l-4 * 4l * [tex]\frac{1}{16}[/tex] + [tex]\frac{1}{3}[/tex] * 3 = l-16l * [tex]\frac{1}{16}[/tex] + 1 = 16 * [tex]\frac{1}{16}[/tex] + 1 = 1 + 1 = 2
y = -[tex]2^{2}[/tex] * ([tex]\frac{\sqrt[3]{4} }{2}[/tex][tex])^{3}[/tex] = -4 * ([tex]\frac{4 }{2^{3}}[/tex]) = -4 * [tex]\frac{4}{8}[/tex] = -2
z = (-1,6[tex])^{0}[/tex] - ([tex]\frac{1}{2}[/tex][tex])^{2}[/tex] + [tex]\sqrt{2\frac{1}{4}[/tex] = 1 - [tex]\frac{1}{4}[/tex] + [tex]\sqrt{\frac{9}{4} }[/tex] = 1 - [tex]\frac{1}{4}[/tex] + [tex]\frac{3}{2}[/tex] = 1 - [tex]\frac{1}{4}[/tex] + [tex]1\frac{2}{4}[/tex] = [tex]2\frac{1}{4}[/tex]
y<x<z
A-3
Szczegółowe wyjaśnienie: